Integration of Artificial Intelligence and Retention Intention: The Role of Adaptability and Employee Engagement in the Era of Digital Transformation - Nugroho, Rio Fajar; Widhianingrum, Wahna; Rapini, Titi (Jurnal Ilmiah Sumber Daya Manusia, 2026)
This study aims to analyze the role of employee attachment in mediating the integration of artificial intelligence with retention intention with adaptability as a moderation variable in employees of BPJS Employment Madiun Branch Office. This study applied a quantitative approach using a sample of primary data from 35 respondents, namely all employees of BPJS Employment Madiun Branch Office. The data was analyzed using SmartPLS software v.4.1.0.9. The results of the study show that the integration of artificial intelligence and employee engagement has a positive and significant effect on retention intention. Employee engagement can mediate the relationship between the integration of artificial intelligence and retention intention, and the existence of adaptability can strengthen the relationship between the two. This research offers novelty by integrating artificial intelligence as a strategic factor in human resource management, analyzing not only its direct influence on retention intention but also through the psychological mechanisms of employee engagement as a mediating variable and adaptability as a moderating variable. This is different from previous research that has generally focused on the impact of technology or employee engagement separately.